Characteristics and Maternal Neonatal Outcomes Analysis of Referral Cases at Lakipadada Regional Public Hospital, Tana Toraja on Period March-August 2019 - Mengga, Beatrix; B, Prasetyo (UNUSA Press, 2020)
Background: Referral system is often noticed as an obstacle for getting health services because it requires more time, higher cost, health services that are not appropriate with competence, patients are accumulated in several health care facilities that can reduce satisfaction of the patient. The implementation of tiered referral system also experiences obstacles that related to geographical factors, distance, transportation and limitations of health services, therefore it is necessary to have an assessment how the characteristics and outcomes of obstetric referral cases in an area. Objective: To identify the charactheristics of obstetric referral cases and maternal – neonatal outcomes from referral cases at Lakipadada Regional Public Hospital on period March – August 2019. Methods: : This study was a retrospective analysis study using descriptive methods of medical record data in obstetric patients at Lakipadada Regional Public Hospital, Tana Toraja on period March - August 2019. Results: The total number of obstetric referral cases is 218 cases, which 154 cases were referred from inside Tana Toraja itself (the most referrals were from private clinics), 64 cases were referred from outside Tana Toraja (the most referrals were from Enrekang District) with the most referral indication was Prolonged Latent Phase. Vaginal delivery was performed in 86 total of cases, caesarean section was 117 total of cases. Conclusion: In the referral cases, there was still a delay in referring patients which on period March-August 2019, there were 2 maternal death, 2 infant deaths and 5 IUFD.